Concept and First Results of Optical Navigational System - Praczyk, Tomasz; Hożyń, Stanisław; Bodnar, Tadeusz; Pietrukaniec, Leszek; Błaszczyk, Marek; Zabłotny, Michał (Transactions on Maritime Science, 2019)
The paper presents a concept of the optical coastal navigational system. The task of the system is to provide information about object position in coastal areas based on optical information. The system is intended for Autonomous Underwater Vehicles that operate in GPS denied environments. In addition to the concept itself, the paper also outlines the first results achieved during the research on the system.